An assessment of road construction in Walmer Township, Nelson Mandela Bay Municipality, South Africa. (29th April 2019) - Nagar, Manesh; Siyongwana, Pakama Q.
This paper reports on a study carried out in Nelson Mandela Bay Municipality, South Africa. It aims at assessing the road infrastructure provision and the financial sustainability of road infrastructure development from 2004-2011 in Walmer Township. The methodology used in the study was a simple method of overlaying the ordinance survey onto high resolution aerial photographs using Walmer Township as the basic unit of observation. Analysis involved the generation of descriptive statistics and applicable tables which are discussed later. The results showed the variation in the construction costs across time indicating spatial variation in road infrastructure developmental initiatives, discrepancies in budget allocation that favour certain areas, and a discord in the coordination of budget and planning. The study's significance lies in its highlighting of the need to review and redesign the planning of municipal infrastructure (township road) projects if they are to attain financial sustainability.